Revision of the Urophora xanthippe species group, with description of new species (Diptera: Tephritidae) - Namin, Saeed Mohamadzade; Nozari, Jamasb (Zootaxa, 2015)
The xanthippe group of species of the genus Urophora Robineau-Desvoidy, 1830 is revised and keyed. It contains seven species with a yellow area on the scutum medial to the notopleuron: Urophora bakhtiari new species (from flowerheads of Cousinia archibaldii), Urophora dirlbeki new species (from flowerheads of Onopordum acanthium), U. iani Korneyev & Merz 1998, U. impicta (Hering 1942) (= Urophora hermonis Freidberg 1974, new synonym), U. kasachstanica (Richter 1964), U. stalker Korneyev 1985, and U. xanthippe (Munro 1934). All the species are described, illustrated and keyed.